2017
DOI: 10.1159/000486122
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-5p Sensitizes the Response of Her-2 Positive Breast Cancer to Trastuzumab by Reducing Rps6

Abstract: Key WordsHer-2-positive breast cancer • Trastuzumab resistance • MiR-129-5p • RpS6 Abstract Background/Aims: Trastuzumab is an important treatment used for patients with Her-2-positive breast cancer, but an increasing incidence of trastuzumab resistance has been observed clinically during the past decade. Aberrant microRNA (miR) expression levels are correlated with prognosis and response to trastuzumab in breast cancer. MiR-129-5p is downregulated in trastuzumab-resistant human breast cancer cells (JIMT-1), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Several studies have unveiled the regulatory functions of miRNAs in breast cancer. For instance, miR-129-5p was demonstrated to stimulate Her-2-positive breast cancer sensitive to trastuzumab [9]. MiR-212-5p/miR-101 was validated to exert inhibitory influences on breast cancer in some studies [10,11], while miR-1246 promoted breast cancer and its drug resistance, [12] and miR-181a had dual regulatory roles in BRCA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have unveiled the regulatory functions of miRNAs in breast cancer. For instance, miR-129-5p was demonstrated to stimulate Her-2-positive breast cancer sensitive to trastuzumab [9]. MiR-212-5p/miR-101 was validated to exert inhibitory influences on breast cancer in some studies [10,11], while miR-1246 promoted breast cancer and its drug resistance, [12] and miR-181a had dual regulatory roles in BRCA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer remains a leading cause of cancer-related death in women [1][2][3]. Despite increased screening and improved diagnosis and treatment of breast cancer, prognosis remains poor [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous, noncoding small RNA molecules, which bind to the 3 0 untranslated region (3 0 UTR) of the target genes, resulting in mRNA degradation or transcriptional inhibition (Cai et al, 2009;Hayes et al, 2014). Studies have reported that dysregulation of miRNAs participate in various biological processes in cancers, including cell proliferation, differentiation, and apoptosis (Zhang et al, 2005;Bartel, 2009;Lu et al, 2017b). Moreover, emerging evidence has indicated that the acquired drug resistance in cancer cells could be regulated by miRNAs (Ma et al, 2010;Majumder and Jacob, 2011).…”
Section: Introductionmentioning
confidence: 99%